Security scheme design of intelligent lighting system based on blockchain - Yongbin Zhao; Cong Men; Xiao Yang; Xiangyang Liu (Blockchain)
Intelligent lighting systems achieve high energy efficiency through precise control and serve as vital tools for reducing carbon emissions, providing essential data for carbon trading. However, data exchange between the lighting system and the carbon trading system presents several challenges. For instance, data may be maliciously tampered with, and frequent unauthorized access threatens the normal operation of carbon trading. Therefore, this paper proposes a security framework for intelligent lighting systems based on blockchain technology. The framework utilizes a dual-chain structure of Hyperledger Fabric and Ethereum to address the issues of blockchain storage expansion and transaction efficiency, employing smart contracts to ensure the effective processing of lighting data. The security requirements for intelligent lighting data are thoroughly studied and analyzed. Additionally, this paper presents a key distribution scheme based on the RSA encryption algorithm to ensure trusted access control within the system. Through detailed analysis and practical verification of the scheme's security and performance, the framework not only effectively prevents data tampering but also ensures data authenticity and the smooth operation of the system during carbon trading, providing robust support for the security and privacy protection of intelligent lighting systems.